1974
DOI: 10.1172/jci107711
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin STEREOCHEMICAL ASPECTS OF ITS METABOLISM AND THE INTERACTION WITH PHENYLBUTAZONE

Abstract: A B S T R A C T An examination of the metabolic fate of the R and the S isomers of warfarin revealed that the two isomers were metabolized by different routes. R warfarin was oxidized to 6-hydroxywarfarin and was reduced to the (R,S) warfarin alcohol. In contrast, S warfarin was oxidized to 7-hydroxywarfarin and was reduced to the (S,S) warfarin alcohol. S warfarin was also oxidized to 6-hydroxywarfarin.These observations suggested that interactions between warfarin and other drugs might be manifest stereospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(83 citation statements)
references
References 28 publications
2
81
0
Order By: Relevance
“…The enantiomers of warfarin follow different metabolic routes in man (Lewis et al, 1974;Toon et al, 1987). The S-enantiomer is mainly hydroxylated to form 7-hydroxywarfarin (Figure 1), whereas R-warfarin is mainly reduced to its RS alcohol and hydroxylated at the 6-position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enantiomers of warfarin follow different metabolic routes in man (Lewis et al, 1974;Toon et al, 1987). The S-enantiomer is mainly hydroxylated to form 7-hydroxywarfarin (Figure 1), whereas R-warfarin is mainly reduced to its RS alcohol and hydroxylated at the 6-position.…”
Section: Introductionmentioning
confidence: 99%
“…Various P450 isozymes, displaying different regio-and stereoselectivities, have been shown to be involved in the metabolism of warfarin (Guengerich et al, 1982;Rettie et al, 1992). The variety of warfarin metabolizing P450 isozymes offers an explanation for the stereoselective (pharmacokinetic) drug-interactions with R-warfarin (Choonara et al, 1986;Toon et al, 1987;Sutfin et al, 1989;), S-warfarin (Lewis et al, 1974;O'Reilly, 1980), as well as non-stereoselective interactions (O'Reilly et al, 1987) that have been observed. The human cytochrome P450 2C9 has been shown to be a S-warfarin 7-(and to a lesser extent 6-) hydroxylase, and is claimed to be responsible for the bulk of S-warfarin clearance in vivo (Rettie et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that the enantiomers of warfarin and phenprocoumon differ in their pharmacokinetic characteristics and metabolic fate, as well as in their anticoagulant activity in man (O'Reilly, 1971;Hewick & McEwen, 1973;Lewis et al, 1973;Breckenridge et al, 1974;O'Reilly, 1974;Levy, O'Reilly & Wingard, 1974;Lewis et al, 1974;Sellers & Koch-Weser, 1975;Hewick & Shepherd, 1976;Jahnchen et al, 1976;Kelly & O'Malley, 1979). The S(-) enantiomers of these two drugs are twice to five times as potent as the R(+) enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the drug inhibits the metabolism of S-warfarin (more potent enantiomer) while increasing the rate of elimination of R-warfarin. The net effect was an increased anticoagulant response to a single dose of racemic warfarin, but no apparent change in the racemic warfarin half-life 155 . The restricted use of phenylbutazone greatly reduces the chance of this potentially fatal interaction being observed.…”
Section: Drugs Causing Inhibition Of Metabolismmentioning
confidence: 96%